PENGUATAN KAPASITAS PEMERINTAH DESA, MASAYARAKAT DAN SATUAN PENDIDIKAN NON FORMAL (SPNF) DALAM UPAYA PENCEGAHAN DAN PENANGAN ANAK PUTUS SEKOLAH DI KEC. MALAKA TENGAH – KAB. MALAKA – PROV. NUSA TENGGARA TIMUR - Serlina Tince Soares; Abdul Syukur; Frans K Selly; Stofiani Susana Lima; Josephina K Sogen; Nirwaning Makleat (Journal of Community Empowerment, 2026)
Abstract Education fundamentally plays a crucial role in the development and advancement of a nation’s assets, particularly its human resources. Data from the Malaka Regency Statistics Agency (BPS) indicate that the Gross Enrollment Rate (GER) for senior high school in 2024 is 77.50%, meaning that 22.50% of youth of upper-secondary school age are not enrolled in school. Meanwhile, the GER for junior high school stands at 91.03%, and the GER for elementary school reaches 98.80%. The high rate of school dropout at the upper-secondary level also contributes to the low Human Development Index (HDI) in 2024, where Malaka Regency ranks 20th out of 23 regencies/municipalities with a score of 65.13%. This community service activity was conducted offline at the Kletek Village Hall, Central Malaka District. The activity involved 50 participants consisting of school-dropout children and their parents, the management of the Lurumutin Community Learning Center (PKBM), as well as the Head of Kletek Village and village officials. The methods employed included lectures, group discussions, and interviews. The results of this activity show an increase in community awareness regarding the importance of the 12-year compulsory education policy, the establishment of collaboration among village authorities, the community, and PKBM in preventing and addressing school dropout cases, marked by the signing of an integrity pact for dropout prevention, and the enrollment of seven school-dropout children into the Package C Equivalency Program at PKBM Lurumutin. Keywords: school dropouts, gross enrollment rate, human development index Abstrak Pendidikan sejatinya memiliki peran yang sangat penting bagi pembangunan dan pengembangan aset-aset negara terutama sumber daya manusia. Data dari BPS Kabupaten Malaka menunjukan bahwa Angka Partisipasi Kasar (APK) Sekolah Menengah Atas tahun 2024 sebesar 77,50 % artinya bahwa sebesar 22,50 % anak usia SMA/sederajat tidak mengenyam pendidikan di sekolah. Sedangkan APK SMP/sederajat adalah 91,03% dan APK jenjang SD/sederajat sebesar 98,80%. Tingginya angka putus sekolah pada tingkat SMA/sederajat juga menjadi penyebab rendahnya Indeks Pembangunan Manusia tahun 2024, dimana Kabupaten Malaka menempati posisi ke-20 dari total 23 Kabupaten/Kota dengan skor 65,13%. Kegiatan pengabdian ini dilaksanakan secara luring bertempat di Balai Desa Kletek Kecamatan Malaka Tengah. Kegiatan pengabdian ini diikuti 50 peserta yang terdiri dari anak dan orangtua kasus putus sekolah, pengelola Pusat Kegiatan Belajar Masyarakat (PKBM) Lurumutin serta Kepala Desa Kletek beserta perangkat. Metode yang digunakan yaitu ceramah, diskusi dan wawancara. Hasil yang diperoleh dari kegiatan ini adalah terjadi peningkatan kesadaran masyarakat akan pentingnya wajib belajar 12 tahun, terciptanya kolaborasi antar pemerintah desa, masyarakat dan PKBM dalam upaya pencegahan dan penanganan anak putus sekolah berupa penandatanganan pakta integritas pencegahan anak putus sekolah serta sebanyak tujuh anak putus sekolah mendaftar Program Kesetaraan Paket C di PKBM Lurumutin. Kata kunci : anak putus sekolah, angka partisipasi kasar, indeks pembangunan manusia